China's telecommunications revolution - Harwit, Eric (Oxford University Press, 2008)
China's telecommunications industry has seen revolutionary transformation and growth over the past three decades. Chinese Internet users number nearly 150 million, and the PRC expects to quickly pass the US in total numbers of connected citizens. The number of mobile and fixed-line telephone users soared from a mere 2 million in 1980 to a total of nearly 800 million in 2007. China has been the most successful developing nation in history for spreading telecommunications access at an unparalleled rapid pace